2007
DOI: 10.1109/tpwrs.2007.908472
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Agent Systems for Power Engineering Applications—Part II: Technologies, Standards, and Tools for Building Multi-agent Systems

Abstract: T. (2007) Multi-agent systems for power engineering applicationspart 2: technologies, standards and tools for building multi-agent systems. IEEE Transactions on Power Systems, 22 (4). pp. 1753-1759.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
168
0
11

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 449 publications
(179 citation statements)
references
References 17 publications
0
168
0
11
Order By: Relevance
“…This step is modeled by the optimization problem (10). The producer procures and activates flexibility services based on the solution of problem (11).…”
Section: Producer and Retailermentioning
confidence: 99%
See 1 more Smart Citation
“…This step is modeled by the optimization problem (10). The producer procures and activates flexibility services based on the solution of problem (11).…”
Section: Producer and Retailermentioning
confidence: 99%
“…Agent-based modeling has been extensively used in the literature to model electric systems [10][11][12][13]. The OPTI-MATE open platform is an example of an agent-based tool used in power systems.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages (e.g., scalability, autonomy and intelligence) are illustrated through a case study describing a SCADA system for electricity transportation management. In [6,7] the authors focus on the application of MAS to power engineering, where problems are formalized, technologies are discussed, and several implementation issues are addressed. In [10] it is reported that MAS technologies outperform classical technologies in the protection of power distribution systems.…”
Section: Related Workmentioning
confidence: 99%
“…BDI agents have been used to develop SCADA systems by treating system components as autonomous agents, to provide better scalability, autonomy and intelligence [6,7,2]. Each agent's beliefs (knowledge about the environment), desires (goals), and intentions (commitments to act) are explicitly represented.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent reviews show that multi-agent systems research in the power systems domain is well-established [18,36,66,67,83,92]. While their original application was often for power system market simulation [85], they have also been used in the context of power system stability control [71].…”
Section: Introduction: Resilience In Power System Coordination and Controlmentioning
confidence: 99%